Encourage Purchase Decisions at J.CO Donuts with Brand Image, Positive Word of Mouth, Social Media Promotion and Location - Nugraheni, Tri Indah; Hidayati, Luk Luk Atul (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
The purpose of this study is to determine the effect of brand image, positive word of mouth, social media promotion and location on purchasing decisions. The sample criteria used in this study were consumers who had bought J.CO Donuts more than once. The sampling method is purposive sampling with a total sample of 100 respondents. The analytical tool used is multiple linear regression with the help of SPSS 25.0 software. The results of this study indicate that brand image, positive word of mouth, social media promotion and location have a positive and simultaneous effect on purchasing decisions. Partially, brand image, social media promotion and location have a positive and significant effect on purchasing decisions, while positive word of mouth has no effect on purchasing decisions.